STATE REGULATION OF THE SPHERE OF MODERN INFORMATION TECHNOLOGIES AND INNOVATIONS: FOREIGN EXPERIENCE - Avedyan L. Y. (Pressing Problems of Public Administration, 2017)
Issues related to the consideration of existing models of regulation of the sphere of innovations and technologies are considered on the example of the leading powers, in other words, the international experience of streamlining of information relations in the society, which will help to identify the essential features of the practical implementation of the information function of the state.